Selecta Capita of Mathematics E-Book for SHS on Contextual Teaching and Learning (CTL) Approach - Octaria, Dina; Kesumawati, Nila; Retta, Allen Marga (Kreano, Jurnal Matematika Kreatif-Inovatif, 2022)
Selecta capita of mathematics is a subject that discusses algebra, geometry, and high school calculus material. Students face obstacles during the learning process: misconceptions about studying selecta capita of mathematics and the lack of electronic textbooks. Therefore, it is necessary to have electronic textbooks that can help students to solve problems by prioritizing independence in the learning process. This study aims to produce a selecta capita of mathematics e-books for SHS on a reasonable and practical contextual teaching and learning (CTL) approach and to see the effectiveness of the e-book that has been developed. The development of selecta capita of mathematics e-book for SHS on CTL approach refers to ADDIE development model. The instruments used to determine the quality of a developed e-book are (1) questionnaires to measure the validity, (2) student response questionnaires to measure practicality, and (3) learning outcomes test questions. The results showed that selecta capita of mathematics e-books for SHS based on the CTL approach developed was good quality and could be used in learning.Kapita selekta matematika merupakan mata kuliah yang membahas materi aljabar, geometri dan kalkulus sekolah menengah atas. Salah satu kendala yang dihadapi peserta didik selama proses pembelajaran yaitu terdapat miskonsepsi dalam mempelajari kapita selekta matematika serta masih minimnya buku ajar elektronik. Oleh karena itu, diperlukan adanya bahan ajar elektronik yang dapat membantu peserta didik memecahkan permasalahan dengan mengutamakan kemandirian dalam proses pembelajaran. Penelitian ini bertujuan untuk menghasilkan e-book kapita selekta matematika SMA berbasis pendekatan contextual teaching and learning (CTL) yang valid dan praktis, serta melihat keefektifan e-book yang telah dikembangkan. Pengembangan e-book kapita selekta matematika SMA berbasis pendekatan CTL mengacu pada model pengembangan ADDIE. Instrumen yang digunakan untuk mengetahui kualitas e-book yang dikembangkan, yakni: (1) angket untuk mengukur kevalidan; (2) angket respon peserta didik untuk mengukur kepraktisan; (3) soal tes hasil belajar. Hasil penelitian menunjukkan e-book kapita selekta matematika SMA berbasis pendekatan CTL yang telah dikembangkan berkualitas baik dan dapat digunakan dalam pembelajaran.